BLOGGING: A STUDY ON THE AWARENESS OF SECONDARY SCHOOL TEACHERS - Rany S and Simi Aravind (PEDAGOGICS: A Journal from School of Pedagogical Sciences, 2017)
Blogs has been widely used in education since the emergence. Web supported teaching and learning activities has become wide spread in educational environments over past decade. Present study indents to find out awareness of secondary school teachers on blogging. Survey method was selected for the study. The study was conducted on a sample of 100 secondary school teachers. The tool used for the study was a questionnaire developed by the investigator to find out the awareness of secondary school teachers on blogging. The data has been analyzed using simple statistics. The study revealed that the awareness of secondary schoolteachers on blogging is not satisfactory even in this technological era.